Site-specific drivers of sensor-based nitrogen management in on-farm corn and wheat experiments - Paccioretti, Pablo; Puntel, Laila; Córdoba, Mariano; Mieno, Taro; Ferguson, Richard; Luck, Joe; Thompson, Laura; Balboa, Guillermo (Frontiers in Agronomy, 2025)
Optimizing nitrogen (N) fertilization is essential for enhancing nitrogen use efficiency (NUE), maximizing crop yields, and minimizing environmental impacts. Sensor-based technologies, integrated with variable rate applications, present a promising approach to site-specific N management. However, their effectiveness can differ across crops, soils, and topographic properties. This study compared sensor-based N management with conventional grower practices in corn and wheat over 17 on-farm site-years. Additionally, we evaluated key site-specific factors influencing sensor performance on a 57 on-farm trial dataset. Our results showed that sensor-based N management significantly improved NUE in corn compared to Grower conventional practices, reducing on average 40 kg N ha-1 without compromising yield. However, in wheat, the differences were not statistically significant across all trials, suggesting that crop-specific responses affect sensor effectiveness. Our findings highlight that corn field yield productivity, its variability, and soil texture were the most influential factors affecting sensor-based NUE. Sensor-based approach in corn outperformed grower practices in moderate to high-variability fields. These results suggest that while sensor-based N management enhances NUE in corn, its effectiveness in wheat may vary more. This study provides valuable insights into the practical limitations and site-specific factors influencing the success of sensor-based technologies, aiding in developing improved decision-support tools for precision nitrogen management.